2022
DOI: 10.3389/fendo.2022.983160
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and inflammation mediate the association of abdominal obesity with colorectal cancer risk

Abstract: BackgroundThe close association of abdominal obesity rather than general obesity with colorectal cancer (CRC) risk might be mediated by IR and inflammation, which has never been systematically explored in large-scale prospective studies.MethodsWe prospectively examined the mediation effects of the fasting triglyceride-glucose (TyG) index and C-reactive protein (CRP) on the associations of obesity (general and abdominal) with CRC risk among 93,659 participants. We used the Cox proportional hazards regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In another pooled cross-sectional study of a population undergoing elective outpatient colonoscopy (n = 646), Whalen et al reported that adherence to PD may reduce systemic inflammation and oxidative stress levels in humans [ 23 ]. This finding partially supports our conclusion since the progression of CRC is typically associated with inflammation and oxidative stress [ 24 26 ]. In addition, epidemiological studies have increasingly confirmed the potential association between adherence to the PD and a reduced risk of other cancers.…”
Section: Discussionsupporting
confidence: 90%
“…In another pooled cross-sectional study of a population undergoing elective outpatient colonoscopy (n = 646), Whalen et al reported that adherence to PD may reduce systemic inflammation and oxidative stress levels in humans [ 23 ]. This finding partially supports our conclusion since the progression of CRC is typically associated with inflammation and oxidative stress [ 24 26 ]. In addition, epidemiological studies have increasingly confirmed the potential association between adherence to the PD and a reduced risk of other cancers.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown in earlier research that inflammation and the TyG index are highly related. Li et al [ 23 ] demonstrated that higher levels of inflammation and the TyG index, both individually and in combination, increased the risk of colorectal cancer. Moreover, Yan et al [ 24 ] elucidated that among Americans under 60 with average weight and no diabetes, the TyG index was positively linked with arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Lee et al also demonstrated that while combined exposure to systemic inflammation and insulin resistance can effectively predict cancer-related mortality in patients, they found that the predictive ability of inflammation remained regardless of insulin resistance levels [ 34 ]. Li et al [ 35 ] showed that metabolic disorders synergistically increase the risk of colorectal cancer and abdominal obesity induced by inflammation, exerting a significant mediating effect. These findings, including both basic and clinical research, collectively suggest that inflammation is more likely to be the initiating factor for metabolic dysregulation and disease than the reverse.…”
Section: Discussionmentioning
confidence: 99%